The genetic architecture of gene expression regulation in a Citrus x Poncirus hybrid tolerant to Huanglongbing - Diaz, Isaac A.; Zayed, Omar; Ávila De Dios, Emmanuel; Jiang, Claire; Bowman, Kim D.; Seymour, Danelle K. (Frontiers in Plant Science, 2025)
Interspecific hybridization is a common and effective strategy for producing disease resilient citrus cultivars, including those with tolerance to Huanglongbing (HLB) disease. Several HLB-tolerant cultivars have been developed through hybridization of mandarins (Citrus reticulata) with their wild relative Poncirus trifoliata. One such cultivar, ‘US-897’, exhibits robust tolerance to the bacteria causing HLB disease, Candidatus Liberibacter asiaticus (CLas). To explore the genetic architecture of the early transcriptional response to Candidatus Liberibacter asiaticus (CLas) infection in ‘US-897’, we performed transcriptomic analysis of the hybrid and its parents, ‘Cleopatra’ (C. reticulata) and ‘Flying Dragon’ (P. trifoliata). A haplotype-resolved genome for ‘US-897’ was generated using PacBio HiFi sequencing reads to support quantification of the expression of both the Citrus and Poncirus alleles. By profiling gene expression in this parent-offspring trio, we were able to determine the mode of inheritance for genes differentially expressed between parents (‘Cleopatra’ and ‘Flying Dragon’) and their interspecific hybrid (‘US-897’), with the majority genes exhibiting non-additive patterns of gene expression inheritance. Additionally, analysis of allele-specific expression in the hybrid ‘US-897’ revealed the contribution of cis- versus trans-acting regulatory variants on genes with additive and non-additive modes of inheritance. A strong correlation between differential expression between parents and allele-specific expression in ‘US-897’ suggests that cis-regulatory variation is a significant source of expression divergence between species. Finally, genes responsive to infection with CLas were identified to explore how gene regulation associated with tolerance to HLB was rewired between Citrus and its relative Poncirus.